Analisis Penerapan SAK EMKM dalam Praktik Akuntansi: (Studi Kasus pada Usaha Kedai Nduy) - Anis Fitriyani; Faiz Azzam Attamimi; Aninda Nuraini; Chania Cahayaningrum; Ibnu Wahyuda (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
This study was conducted to examine the level of implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) at Kedai Nduy, a micro-scale culinary business located in Depok. The basis for conducting this research is the low quality of financial records among UMKM players due to a lack of understanding of accounting, limited assistance from competent parties, and the suboptimal implementation of financial reporting standards, which are the main obstacles. This research was conducted using a descriptive qualitative method, where data was collected through interviews, direct observation, and document searches related to transaction recording activities, sales, raw material purchases, and daily cash flow. The results of the study show that Kedai Nduy has consistently recorded transactions using a simple financial recording format using Excel tables, but the implementation does not fully comply with SAK EMKM provisions. This business entity has also not prepared the required financial statements, namely the Statement of Financial Position, Income Statement, and Notes to the Financial Statements. The main obstacles faced are limited understanding of accounting, lack of time available to business owners, and the unavailability of technical assistance and accounting training. Nevertheless, simple record keeping still provides benefits, particularly in monitoring sales, purchasing, and daily cash flow activities. Therefore, this study recommends accounting training, the use of SAK EMKM-based applications or templates, and ongoing assistance to improve the quality of financial recording and reporting in accordance with applicable standards.